BS EN 1657 Chemical disinfectants and antiseptics - Quantitative suspension test for the evaluation of fungicidal or yeasticidal activity of chemical disinfectants and antiseptics used in the veterinary area. Test method and requirements (phase 2, step 1). (10th May 2023) - British Standards Institution,
No abstract available